2019
DOI: 10.1055/s-0039-1685503
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Non-Beta-lactam Antibiotics for Prevention of Cesarean Delivery Surgical Site Infections

Abstract: Objective To examine the association between perioperative Beta (β))-lactam versus non-β-lactam antibiotics and cesarean delivery surgical site infection (SSI). Study Design Retrospective cohort of women undergoing cesarean delivery from January 1 to December 31, 2014. All women undergoing cesarean after 34 weeks with a postpartum visit were included. Prevalence of SSI was compared between women receiving β-lactam versus non-β-lactam antibiotics. Bivariate analyses were performed using Pearson's Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…This association was likely due to fewer surgical site infections with cefazolin, which is concordant with 2 recent studies conducted at a single academic institution and using the same MFMU dataset as the current study, showing the protective effect of cefazolin more generally for surgical site infection among women delivering by cesarean delivery who did not have chorioamniontis. 19,20 A similar association with cefazolin has also been noted with regard to surgical site infection after hysterectomy.21 The decreased risk of surgical site infection with cefazolin may be due to its efficacy against skin flora, including Streptococcus species, Staphylococcus aureus, and coagulase-negative Staphylococcus. 37,38 In the current study, the observed finding was despite the fact that women treated with cefazolin were less likely to receive postpartum antibiotics compared to those treated with clindamycin or gentamicin.…”
Section: Resultsmentioning
confidence: 81%
“…This association was likely due to fewer surgical site infections with cefazolin, which is concordant with 2 recent studies conducted at a single academic institution and using the same MFMU dataset as the current study, showing the protective effect of cefazolin more generally for surgical site infection among women delivering by cesarean delivery who did not have chorioamniontis. 19,20 A similar association with cefazolin has also been noted with regard to surgical site infection after hysterectomy.21 The decreased risk of surgical site infection with cefazolin may be due to its efficacy against skin flora, including Streptococcus species, Staphylococcus aureus, and coagulase-negative Staphylococcus. 37,38 In the current study, the observed finding was despite the fact that women treated with cefazolin were less likely to receive postpartum antibiotics compared to those treated with clindamycin or gentamicin.…”
Section: Resultsmentioning
confidence: 81%
“…Literature shows that administration of non- β -lactam prophylaxis increases the risk of adverse surgical outcomes including SSI [ 1 3 , 18 , 41 ]. Hopkins et al and Harris et al separately retrospectively analyzed the prevalence of CD SSI between women who received perioperative β -lactam vs. non- β -lactam prophylaxis [ 1 , 2 ]. Both studies showed that patients who received non- β -lactam antibiotics were more likely to have a wound complication, including infection, versus those who received β -lactam antibiotics (14.6% vs. 6.7% by Hopkins et al and 15% vs. 7% by Harris et al) [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hopkins et al and Harris et al separately retrospectively analyzed the prevalence of CD SSI between women who received perioperative β -lactam vs. non- β -lactam prophylaxis [ 1 , 2 ]. Both studies showed that patients who received non- β -lactam antibiotics were more likely to have a wound complication, including infection, versus those who received β -lactam antibiotics (14.6% vs. 6.7% by Hopkins et al and 15% vs. 7% by Harris et al) [ 1 , 2 ]. Thus, these studies identified an increased odd of SSI with non- β -lactam prophylaxis consistent with our findings (aOR = 1.43; 95%CI = 1.01–2.02; p = 0.045) [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In women who report a penicillin allergy, the inability to utilize a β-lactam antibiotic during pregnancy has been associated with less effective intrapartum neonatal group B streptococcus (GBS) prophylaxis, a greater rate of cesarean surgical site infection and increased risk of postpartum endometritis. [4][5][6] However, when penicillin allergy testing is performed in individuals who report a history of a penicillin allergy, the majority do not exhibit a positive reaction. 7 Despite penicillin allergy testing being shown to be safe during pregnancy, it is rarely performed.…”
mentioning
confidence: 99%